2021
DOI: 10.1055/a-1403-2701
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Nonivamide-nicoboxil on the Peak Power Output in Competitive Sportsmen

Abstract: Recent studies have shown that the oxygenated hemoglobin level can be enhanced during rest through the application of nonivamide-nicoboxil cream. However, the effect of nonivamide-nicoboxil cream on oxygenation and endurance performance under hypoxic conditions is unknown. Therefore, the purpose of this study was to investigate the effects of nonivamide-nicoboxil cream on local muscle oxygenation and endurance performance under normoxic and hypoxic conditions. In a cross-over design, 13 athletes (experienced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…as a means of enhancing muscle performance or recovery). The following situations were compared with some control scenarios to evaluate the muscle oxygenation responses and the potential benefits of the tested product or intervention: the use of a tracksuit jacket with heating elements [ 162 ], nonivamide-nicoboxil cream [ 180 ], sports compression garment ( n = 3 for lower limb: tights, calf sleeve, socks; n = 1 for upper limb, forearm) [ 18 , 19 , 31 , 107 ], core and skin cooling [ 136 ], undergoing thigh cooling by a water-circulating pad [ 85 ] and oral supplementation with dietary inorganic nitrate-rich and placebo beetroot juice [ 32 , 33 , 40 , 43 , 63 , 75 , 76 , 131 , 146 , 158 , 183 , 190 , 201 ], supplementation with pomegranate extract and co-supplementation with N -acetylcysteine [ 39 ], protein powder [ 134 ], pre-exercise ingestion of a drink with higher dissolved O 2 [ 135 ], anthocyanin-rich New Zealand blackcurrant supplementation [ 27 ], 1 h after a single dose of mango leaf extract rich in mangiferin and lecithin, or mango leaf extract rich in mangiferin and quercetin, phospholipids addition [ 53 55 ], red spinach extract [ 121 ], citrulline drink/citrulline malate [ 190 , 196 ], l -arginine [ 141 , 143 ], Montmorency cherry polyphenols [ 67 ], eicosapentaenoic acid and docosahexaenoic acid (fish oil) [ 198 ], caffeine intake [ 189 ] and dark chocolate [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…as a means of enhancing muscle performance or recovery). The following situations were compared with some control scenarios to evaluate the muscle oxygenation responses and the potential benefits of the tested product or intervention: the use of a tracksuit jacket with heating elements [ 162 ], nonivamide-nicoboxil cream [ 180 ], sports compression garment ( n = 3 for lower limb: tights, calf sleeve, socks; n = 1 for upper limb, forearm) [ 18 , 19 , 31 , 107 ], core and skin cooling [ 136 ], undergoing thigh cooling by a water-circulating pad [ 85 ] and oral supplementation with dietary inorganic nitrate-rich and placebo beetroot juice [ 32 , 33 , 40 , 43 , 63 , 75 , 76 , 131 , 146 , 158 , 183 , 190 , 201 ], supplementation with pomegranate extract and co-supplementation with N -acetylcysteine [ 39 ], protein powder [ 134 ], pre-exercise ingestion of a drink with higher dissolved O 2 [ 135 ], anthocyanin-rich New Zealand blackcurrant supplementation [ 27 ], 1 h after a single dose of mango leaf extract rich in mangiferin and lecithin, or mango leaf extract rich in mangiferin and quercetin, phospholipids addition [ 53 55 ], red spinach extract [ 121 ], citrulline drink/citrulline malate [ 190 , 196 ], l -arginine [ 141 , 143 ], Montmorency cherry polyphenols [ 67 ], eicosapentaenoic acid and docosahexaenoic acid (fish oil) [ 198 ], caffeine intake [ 189 ] and dark chocolate [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of sports creams can be considered the cause of this change. Sports cream is a blood-circulation-promoting cream that produces heat [28]. Previous studies have shown a significant increase in tissue blood flow when heat wraps are used [29].…”
Section: Discussionmentioning
confidence: 99%